Study To Evaluate The Add On Effect Of Atasi On Type 2 Diabetes Mellitus - Tripathi, Madhuri; Jain, Trupti; Bansal, Charu (International Research Journal of Ayurveda & Yoga, 2020)
Diabetes is a silent killer affecting millions and millions of people and poses a grave threat to the earth’s population. Previously Diabetes has considered as a disorder of elderly, now a day’s status has changed, and it has become a major cause of morbidity and mortality affecting the youth and middle aged people. On etiological basis Diabetes has classified into two main types as type 1 and type 2. Type -2 Diabetes Mellitus is a metabolic disorder presented by Hyperglycemia due to defects in insulin secretion, action or both. Both forms of Diabetes can lead to several microvascular and macrovascular multisystem complications. One way to keep diabetes and its complications under control is; early detection of the disease and to adopt the healthy lifestyle. W.H.O. emphasizes on the using of traditional drugs with the lowest side effects to control Diabetes symptoms. Ayurvedic literature explains it under the heading of Prameha/Madhumeha. Madhumeha (subtype of Vataj Prameha) is a disease which resembles with Diabetes Mellitus. Type 2 Diabetes Mellitus is mainly associated with Avaranjanya samprapti and sthool pramehi or Apathyanimittaja Pramehi can be correlated to patients of Type 2 Diabetes Mellitus. Acharya Sushrutha and Charaka emphasized the importance of diet and exercise in the management of Diabetes. Both has mentioned that patients of Diabetes should take the diet combined with Flaxseed oil (C.Chi.6/20, S. Chi.31/5) and several researches also proved the positive effect of Atasi on inflammation, glycemic control and oxidative stress. Thus for present study Atasi has selected and clinical trial was conducted on 60 patients of Type 2 D.M. for 45 days. These patients were divided into 2 groups as group A (Atasi) and group B (Placebo). After 45 days, results showed significant improvement on subjective and objective parameters in group A i.e. Atasi group